Determining of right-hand side of higher order ultraparabolic equation - Protsakh Nataliya (Open Mathematics, 2017)
In the paper the conditions of the existence and uniqueness of the solution for the inverse problem for higher order ultraparabolic equation are obtained. The equation contains two unknown functions of spatial and time variables in its right-hand side. The overdetermination conditions of the integral type are used.